The big short : inside the doomsday machine - Lewis, Michael (Michael M.) (W.W. Norton & Co., 2010)
The author examines the causes of the U.S. stock market crash of 2008 and its relation to overpriced real estate, bad mortgages, shareholder demand for excessive profits, and the growth of toxic derivatives.